Nkanelo wa micino ya Ndhhavuko Machangana hi ku kongomisa eka miganga ya sangwe na sengwe exifundzeni xa Chiredzi - Zimbabwe - Watungwa, Joice (My University, 2017)
This study attempts to describe and understand the nature of Xangani traditional dances in Chiredzi District of Zimbabwe. Regrettably for the Xangani not so many literal works have been produced on their dances and it is this lack of documentation that has created gaps. This research has been designed to narrow such notable gaps within the Xangani culture. In this research the major prevalent among the Xangani people, the socio-economic and political values of dances as well the instrument, dress and music that accompany the Xangani traditional dances shall be looked into significantly. To achieve this, a sample of the population was studied and the results were inferred to the generality of the whole community population. Permission was sought from the community leaders and sampled people were interviewed, their views were collected through observation. The research was triangulate to minimize bias and also ensured that efficiency was enhanced. The study considered desktop data as well as written and oral tradition as sources of information on this research.
MAAS (Xitsonga)
Ehansi ka Senthara ya M.E. R. Mathivha ya Tindzimi ta Afrika, Vutshila na Ndhavuko
Keywords: Ncino; UCTD; Ndhavuko wa Machangana; Mfuwo wa rixaka; Risimu; Vaakatiko; 793.3196891; Folk dancing -- South Africa; Folk dancing -- Zimbabwe; Musical instruments -- South Africa -- Limpopo; Musical instruments -- Zimbabwe